Protein-RNA and Protein-Protein Recognition by Dual KH1/2 Domains of the Neuronal Splicing Factor Nova-1 - Teplova, Marianna (2011)
Nova onconeural antigens are neuron-specific RNA-binding proteins implicated in paraneoplastic opsoclonus-myoclonus-ataxia (POMA) syndrome. Nova harbors three K-homology (KH) motifs implicated in alternate splicing regulation of genes involved in inhibitory synaptic transmission. We report the crystal structure of the first two KH domains (KH1/2) of Nova-1 bound to an in vitro selected RNA hairpin, containing a UCAG-UCAC high-affinity binding site. Sequence-specific intermolecular contacts in the complex involve KH1 and the second UCAC repeat, with the RNA scaffold buttressed by interactions between repeats. While the canonical RNA-binding surface of KH2 in the above complex engages in protein-protein interactions in the crystalline state, the individual KH2 domain can sequence-specifically target the UCAC RNA element in solution. The observed anti-parallel alignment of KH1 and KH2 domains in the crystal structure of the complex generates a scaffold that could facilitate target pre-mRNA looping upon Nova binding, thereby potentially explaining Nova’s functional role in splicing regulation.